2011
DOI: 10.1177/1469605311403852
|View full text |Cite
|
Sign up to set email alerts
|

When knowledges meet: Engagements with clay and soil in southern Africa

Abstract: In what ways do meetings between differing knowledges of the material world involve change to people's engagements with their immediate, everyday surroundings? And may our insights from studies of such dynamics inform archaeological thinking and practice in fruitful ways without unwillingly projecting ideas and concepts specific to western post-Enlightenment thinking? By combining archaeological and anthropological insights with African philosophical critique, this article presents an approach which aims to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Menkiti employs what he terms an expanded notion of material causation. The implication is that humans and nonhumans alike share the ability for action, belonging to the same undivided plane of material causation (see also Fredriksen 2011). Viewing necropolitics as a version of Menkiti's symmetrical expanded notion may inform our approach to engagements between differing knowledges in our Manica case.…”
Section: A Vernacular Cosmopolitanism: Epistemic Levelling and Heritamentioning
confidence: 93%
See 1 more Smart Citation
“…Menkiti employs what he terms an expanded notion of material causation. The implication is that humans and nonhumans alike share the ability for action, belonging to the same undivided plane of material causation (see also Fredriksen 2011). Viewing necropolitics as a version of Menkiti's symmetrical expanded notion may inform our approach to engagements between differing knowledges in our Manica case.…”
Section: A Vernacular Cosmopolitanism: Epistemic Levelling and Heritamentioning
confidence: 93%
“…For many rural communities on the sub-continent this involves at least one mis-categorization: of the members of the local community that are seen as fundamental to any decision-making of importance, namely the dead. By questioning conventional understanding of the notion of politics we relate to recent analyses of how meetings between differing knowledges of the material world involve changes to people's engagement with their physical surroundings (Fredriksen 2011(Fredriksen , 2012. This challenges the way we think of and engage with material and immaterial heritage.…”
Section: A Vernacular Cosmopolitanism: Epistemic Levelling and Heritamentioning
confidence: 99%
“…Such perceptions are at least partly embedded in the material properties of clay, which make it feel like a living substance and capable of engendering a range of responses, sensations and emotions in people. This character of clay presumably contributed to the animistic–shamanistic and magical associations proposed for prehistoric clay work (Fredriksen ; Herva et al . , 147–9).…”
Section: The Importance and Affordances Of Clay And Clay Workmentioning
confidence: 93%
“…Several scholars have also observed that clay was a special substance in the Stone Age world owing to its specific properties. Clay is an ambiguous or ‘indeterminate’ material ranging between fluid and solid; it is malleable and can be worked directly by hand; it can be worked by adding (and not only reducing) material and reworked endlessly; and it turns into a different kind of substance when fired (Wengrow ; Gheorghiu ; Timmons and MacDonald ; Fredriksen ). These very properties of clay promoted, in Boivin's () view, the Neolithic explosion of symbolism.…”
Section: The Importance and Affordances Of Clay And Clay Workmentioning
confidence: 99%
See 1 more Smart Citation